2022
DOI: 10.1007/s00423-022-02578-6
|View full text |Cite
|
Sign up to set email alerts
|

Textbook outcome among voluntary donors undergoing major living donor hepatectomy

Abstract: Purpose Textbook outcome (TO) is a composite measure of outcome and provides superior assessment of quality of care after surgery. TO after major living donor hepatectomy (MLDH) has not been assessed. The objective of this study was to determine the rate of TO and its associated factors, after MLDH. Methods This was a single center retrospective review of living liver donors who underwent MLDH between 2012 and 2021 ( n = 1022). The rate of TO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…Another major finding is this study is that TO was achieved in the overwhelming majority (92.2%) of patients who underwent living donor right hepatic lobectomy. This is significantly higher than previously reported by Bhatti et al 4 who found that 69.4% of right lobe donor hepatectomy patients achieved a TO, and which to our knowledge is the only other study to report TO in this surgical population. Moreover, Rössler et al 18 reviewed 4206 living donor right hepatectomies and reported on individual outcome parameters in an effort to serve as a benchmark for hepatic surgery, but they did not utilize a composite outcome measure.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Another major finding is this study is that TO was achieved in the overwhelming majority (92.2%) of patients who underwent living donor right hepatic lobectomy. This is significantly higher than previously reported by Bhatti et al 4 who found that 69.4% of right lobe donor hepatectomy patients achieved a TO, and which to our knowledge is the only other study to report TO in this surgical population. Moreover, Rössler et al 18 reviewed 4206 living donor right hepatectomies and reported on individual outcome parameters in an effort to serve as a benchmark for hepatic surgery, but they did not utilize a composite outcome measure.…”
Section: Discussioncontrasting
confidence: 67%
“…An additional quality improvement tool is benchmarking, which attempts to identify the best-achievable outcomes for a specific surgical procedure 5,15–17 . In the field of hepatic surgery, live donor hepatectomy has been proposed as a unique model to benchmark hepatic resections, as the anticipated morbidity of liver donation should be low and mortality should be negligible 4,18 . A recent study reported that TO was achieved in 70% of patients undergoing major live donor hepatectomy, including both right and left hepatic lobectomy 4 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Familiarity with the porta hepatis during donor and recipient operations and small duct-to-duct biliary anastomoses using 7/0 sutures may have been responsible for these outcomes. [33][34][35] Liver resection is required in only 0.8% to 1.4% patients with complex vasculobiliary injury or proximal BDI. 12,17 A recent systematic review showed that only 67 patients underwent right hepatectomy for BDI.…”
Section: Discussionmentioning
confidence: 99%
“…Familiarity with the porta hepatis during donor and recipient operations and small duct-to-duct biliary anastomoses using 7/0 sutures may have been responsible for these outcomes. 33 35 …”
Section: Discussionmentioning
confidence: 99%